Online and Offline Protest Discourse in Modern Russia - Kirill M. Makarenko (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2022)
ntroduction. The article is devoted to the analysis of the formation and spread of protest discourse in new practices of protest behavior. Online rallies, which appeared in 2020 in the public space of Russia, remained an unobtrusive practice, despite their potential applicability within the framework of a single logic of “competitive politics”.